2023
DOI: 10.2147/ppa.s390997
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adherence Level and the Relationship Between Treatment Adherence, and Superstitious Thinking Related to Health Issues Among Chronic Disease Patients in Southern Jordan: Cross-Sectional Study

Abstract: Background: For disease management, numerous drugs are prescribed. However, long-term treatment adherence is still unsatisfactory. Culture influences beliefs regarding medication, particularly irrational ideas that affect treatment adherence. The Middle East, notably Jordan, is affected by a lack of awareness of these attitudes with regard to treatment adherence. Objective: Investigating the adherence level among patients with chronic diseases in southern Jordan. To determine whether certain demographic traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, for individuals with lower levels of education, an increase in health literacy could have a stronger impact on improving medication adherence. Individuals with higher levels of education tend to have higher health demands than those with lower levels of education and tend to understand the importance of medication ( 85 ). Conversely, those with lower levels of education are more likely to make mistakes, have less medical knowledge, and have superstitious beliefs ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for individuals with lower levels of education, an increase in health literacy could have a stronger impact on improving medication adherence. Individuals with higher levels of education tend to have higher health demands than those with lower levels of education and tend to understand the importance of medication ( 85 ). Conversely, those with lower levels of education are more likely to make mistakes, have less medical knowledge, and have superstitious beliefs ( 85 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher levels of education tend to have higher health demands than those with lower levels of education and tend to understand the importance of medication ( 85 ). Conversely, those with lower levels of education are more likely to make mistakes, have less medical knowledge, and have superstitious beliefs ( 85 ). Therefore, they are more likely to make poor decisions when experiencing health problems.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 Other studies from Jordan showed opposite outcomes and concluded that the higher the educational levels the higher adherence level found in patients with heart failure and other chronic condition. 29 , 32 In addition, another study from the USA, indicated that lower educational accomplishment was associated with higher adherence levels in men, but lower adherence levels among women diagnosed with hypertension. 33…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Other studies from Jordan showed opposite outcomes and concluded that the higher the educational levels the higher adherence level found in patients with heart failure and other chronic condition. 29,32 In addition, another study from the USA, indicated that lower educational accomplishment was associated with higher adherence levels in men, but lower adherence levels among women diagnosed with hypertension. 33 Furthermore, our results revealed a strong association between the frequency of medication administration and the level of medication adherence among elderly patients complaining of both diabetes and CVS conditions, indicating that a higher frequency of medications was positively correlated with a higher adherence level.…”
mentioning
confidence: 99%
“…La mala adherencia al tratamiento a largo plazo es un problema multifactorial. Estos factores incluyen la condición crónica de la enfermedad, factores de la terapia (régimen de medicación complejo y polifarmacia, interacciones entre medicamentos y alimentos, costo, efectos adversos), factores del paciente (deterioro de la memoria y la cognición, falta de apoyo y cuidado familiar y social, creencias y percepciones sobre el medicamento) (41). El nivel educativo de los pacientes en el estudio fue en su mayoría secundaria, ello permite a los pacientes tener un mayor acceso a los materiales educativos brindados en el establecimiento de salud, así como una mejor comprensión de las sesiones educativas brindadas, sin embargo, cuando se trabaja con pacientes iletrados, se tiene que buscar otras estrategias para lograr un mejor entendimiento.…”
Section: Discussionunclassified